دراسة مقاومة الصفائح المستخدمة في عمليات التصفيح والمحضرة من المواد المركبة للصدم عالي السرعة - نزار عبد الرحمن; لطيفة الحموي; نورا سليمان (Tishreen University, 2018)
في هذا البحث تم دراسة مقاومة ألواح صفائحية متعددة الطبقات (بنى مركبة) مصنوعة من البولي استر غير المشبع المسلح بالألياف الزجاجية للصدم عالي السرعة، وبإضافة بعض المواد المالئة بهدف استخدامها كطبقات حماية لأغراض التصفيح. ولتحقيق هذا الهدف تم تحضير مجموعة من العينات من مادة البولي استر غير المشبع كمادة أساس بوليميرية والألياف الزجاجية كمادة تدعيم حيث استخدمت ثلاث أنواع من الألياف هي (العشوائية، المنسوجة، الموجهة). أخضعت العينات لاختبار الصدم عالي السرعة (قذائفي) بهدف استقراء قدرة العينات على امتصاص طاقة الصدم ودراسة أنماط التشوه والانهيار الحاصلة. بينت النتائج أن لهذه العينات قدرة على امتصاص جزء من طاقة القذيفة، كما وسجلت أنماطاً معقدة ومختلفة للضرر والتشوه من حيث شكل بروفايل الضرر واتضح أنها تختلف باختلاف نوع الألياف الزجاجية المستخدمة، حيث أظهرت الألياف الموجهة أكبر مساحات للضرر والتشوه وبالتالي أعلى قدرة على امتصاص طاقة الأحمال. بينت النتائج أيضاً أن إضافة المواد المالئة (رمل، براددة حديد) أثر سلباً على النتائج حيث قلل من قدرة العينة على امتصاص طاقة الصدم. In this research, the resistance against high-velocity impact was studied of the laminated composite panels prepared from unsaturated polyester and armed with glass fibers in addition to some fillers in order to improve their properties. To achieve this goal, a set of samples was prepared from unsaturated polyester as a matrix and fiber glass used as a reinforcement material where three types of fibers are used (Mat, Woven, and Unidirectional). The samples were subjected to high-velocity impact test (ballistic) in order to extrapolate the sample's ability to absorb the kinetic energy of the projectile and to study the deformation and failure patterns occurred. As for the testing results, the samples have shown a very good ability to absorb a large part of the projectile energy and recorded complex and different modes in terms of damage and deformation in the form of profile damage. Moreover, it was found that the absorption and energy dissipation increase with the number of layers, and the unidirectional fibers showed the best results. Experiments also exposed that the addition of fillers (sand, iron filings) presented negative results and reduced the sample's ability to absorb impact energy.